EVALUASI PELAKSANAAN PROGRAM BIMBINGAN KARIER DENGAN MODEL CIPP DI SMK NEGERI 2 SALATIGA - Elisabet Septia Atma; Dwikurnaningsih, Yari; Wasitohadi, Wasitohadi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
The research aims to evaluate the implementation of the career guidance program at SMK Negeri 2 Salatiga, based on the Context, Input, Process and Product method. This research is an evaluative research with a qualitative descriptive approach. The data collection techniques used were interviews, observation, and documentation studies. The analysis technique used in this research is the Miles & Hubberman qualitative analysis technique which includes data collection, data reduction, data display, and data verification. The validation test in this research was done using a triangulation of sources and techniques. The results of this research show that: 1) for Context, there are high support from schools, and the goals are prepared in line with the school's vision and mission; 2) ior Input, there are sufficient ratio of teachers to students, availability of budget for program implementation, programs and materials that are prepared based on student and school needs, as well as availability of supporting infrastructure for the implementation of career guidance programs; 3) for Process, procedures are implemented by adopting guidance and counseling services, the evaluation and follow-up are not implemented sufficiently, the student involvement is good, and the school community supports the implementation of career guidance and DUDI participates in program implementation. There are obstacles in implementing the career guidance program, which are: the lack of time due to assignments and busy school activities; 4) for Product, it can be stated that the budget and infrastructure are relatively sufficient, the program implementation is 80%, the impact of implementing career guidance is that students get an idea of ​​career direction.